Peran Organisasi Satuan Siswa Pelajar dan Mahasiswa Pemuda Pancasila dalam Menangkal Paham Radikalisme pada Mahasiswa - Thania, Tira; Lestari, Ria Yuni; Juwandi, Ronni (Universitas Negeri Malang, 2023)
The purpose of writing the article is to discuss the role of the Pancasila Student and Youth Student Unit organization at Sultan Ageng Tirtayasa University in countering radicalism among students. The study uses a qualitative approach with a descriptive type. Data collection uses observation techniques, interviews, and documentation studies. The role of organizations is to ward off radicalism among students through counterradicalization efforts, namely by counter-ideology, counternarrative, and counterpropaganda. Counter-radicalization is carried out by carrying out several activities, namely through organizational introduction orientation activities, routine studies, public discussions, consolidations, orations, posting press releases and study materials, as well as campaigns on the dangers of radicalism. Supporting factors for implementing activities are coordination with the Serang City Pancasila Student and Youth Student Unit and sub-commissariats in the faculty, and collaboration with other organizations. The inhibiting factors faced are the existence of inactive cadres and the lack of participation from students.